TEACHING ENGLISH USING GOOGLE CLASSROOM AS MEDIA AT MTs ARROHMAN JOMBANG - Khudriyah Khudriyah (Ilmuna: Jurnal Studi Pendidikan Agama Islam, 2021)
The goal of learning English in junior high school is students can reach the functional level, namely communicating orally and in writing to solve daily problems. This research aimed to describe how teaching English using Google classroom at MTs arrohman Jombang. The research method is qualitative descriptive, interview and observation as instrument. The data then analysed by Miles & Huberman model. The result are: The process of teaching and learning English: deciding learning objectives, materials, media, and evaluation of all components. The learning objectives were in accordance with the indicators contained in the curriculum. The material conveyed to students were: understanding, function, and application of the past tense in sentences. Using media of power point, pictures, and sheet of students work. The learning method used was questions and answers; the strategy used based on on the students’ condition. And the evaluation results dit not achieve the criteria of success. Those students who were able to reach the criterion was only 50% from A class, and 34% from B class.